Desarrollo de software educativo como apoyo didáctico en el área de estudios sociales del nivel de educación general básica, enmarcado a los hechos históricos, geográficos y educativos del cantón Calvas de la provincia de Loja de la región sur del ecuador, 2011 - Castillo Vega, Nixon Rodrigo (2014)
This research was performed taking into account the rich cultural history that tells the canton Calvas but lacks teaching tools for teaching in educational establishments. Thus is first performed based on an investigation of the historical, cultural , geographical and educational facts Calvas Canton , with the help of some tools such as interviews and direct observation, the different views on a large part of the canton Calvas. Resulting in photographs, videos of tourist attractions, monuments , parks, churches, and attractions. All this information already stored in digital, both text, photos, videos and audio became the core content of educational software. Finished software and complying with the sequence of the waterfall methodology proceeded to socialization and implementation of surveys on the Autonomous Municipal Government Decentralization Canton Calvas and schools Chile, Ambato, and Jenyffer and Jaély Ludeman Jiménez city Cariamanga , resulting in the approval and feasibility of software and ensure the accuracy and functionality of it .